THE URGENCY OF VIRALITY FOR THE DEVELOPMENT OF GEN Z PERSONAL BRANDING ON TIKTOK SOCIAL MEDIA GAME CONTENT IN INDONESIA - Mochamad Afi Adani; Catur Nugroho (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research is based on the virality phenomenon on TikTok social media, especially on game content that occurs in Indonesia, viral content on TikTok social media feels that it can increase user personal branding. The purpose of this study is to find out the tendency of netizen responses to this phenomenon. This study uses a descriptive qualitative research method with data collection using a questionnaire distribution method distributed through social media networks and digital media. interviews, observations, and documentation. This study uses the Likert scale concept, namely a scale that is formed by providing two forms of statements, namely positive and negative, which aim to measure attitudes towards certain objects (Corbetta, 2003; Neuman, 2014) in (Martono, 2023). The classification of distribution in this study is that the distribution is only focused on Gen Z netizens who were born from 1997 to 2012. Based on the results of the study (1) It is known that the response related to the virality variable has a positive response in all points of the instrument that have been given, although there are some who disagree with the related questions. (2) It is known from the results of the TikTok social media variable that it is known to have a positive response in several points of the instrument that have been given, but there are some who disagree with the related questions. (3) It is also known that the response from respondents regarding the personal branding instrument has a positive sentiment, especially when associated with the TikTok social media instrument.